Instagramability and Algorithmic Influence in Travel Intentions: A Bibliometric Mapping of Visual-Driven Tourism - Judijanto, Loso; Kurniawan, Ramdhan; Suharto, Bambang (Westscience Press, 2025)
This paper investigates the convergence of Instagramability, algorithmic impact, and travel intention using an extensive bibliometric analysis of visual-centric tourism research. Utilizing 350 Scopus-indexed documents published from 2010 to 2025, the analysis employs VOSviewer and Biblioshiny to investigate publication trends, subject clusters, and collaborative networks across authors, institutions, and countries. The results indicate three primary research areas: (1) social media and decision-making, (2) sustainable tourism and destination development, and (3) the psychological and behavioral aspects of travel. The topic has transitioned from traditional examinations of tourist motivation to digitally mediated paradigms that prioritize visual communication, influencer marketing, and algorithmic curation. China, the United States, and the United Kingdom have become important places for people from all over the world to work together. There are also strong intellectual links between Asia and Europe. The study advances theoretical frameworks by amalgamating theories of visual communication, algorithmic mediation, and behavioral intention, while also providing practical guidance for destination marketers and policymakers to enhance digital engagement methods. The study, constrained by its dependence on Scopus data, provides a robust basis for subsequent empirical and computational investigations into the interplay between algorithms and visual culture in shaping contemporary travel behavior.